Insights into the pH-driven emulsifying properties and self-assembly behaviour of pea peptides - Xiaoyang Sun; Yan Chen; Xinxin Xu; Pei Wang; Jinhu Tian; Meichen Liu; Xiufeng Zhang; Xiaoqing Yuan; Fusheng Chen; Lifen Zhang (Food Research International, 2026)

Hyperspectral monitoring of wheat gluten index based on multi-model ensemble and adaptive learning - Shiyou Zhu; Juan Bai; Yulong Chen; Jingyu Chen; Caiyu Ji; Yingchao Hao; Sha Yang; Yu Zhao; Meijun Zhang; Meichen Feng; Wude Yang; Guangxin Li (Food Chemistry, 2026)

Iron-regulated crystallization in sensible-heat-driven glass-ceramics from molten lead-zinc smelting slag: Process-structure-property coupling and LCA quantification - Yibo Yang; Yusheng Tang; Hanguang Fu; Mengchen Xiao; Meichen Pan; Jixian Wu; Zhichuan Li; Zhe Tan; Zhixue Qu; Dean Pan; Xiaoguang Zhang (Process Safety and Environmental Protection, 2026)

Decoding the survival strategy of Parachlorella sp. MP1: Genomic basis and physiological adaptations to acidity and heavy metals in acid mine drainage - Meichen Wang; Lu Zhang; Zhengbo Yue; Zijie Yu; Rui Deng; Jin Wang (Bioresource Technology, 2026)

Sustainable Mn-Ni-Co recovery from complex secondary resources through process-chain engineering and life-cycle environmental assessment - Meichen Pan; Yusheng Tang; Ziyuan Liu; Zhe Tan; Yibo Yang; Panpan Mu; Xiaoguang Zhang (Chemical Engineering Journal, 2026)

Antibiotic resistance genes in food wastes: diversity, dynamics, and interactions with prokaryotes and viruses in centralized biogas plants - Chao Zhang; Jiawei Sun; Zhijian Shi; Meichen Sun; Qianqi Shao; Shicheng Zhang; Gang Luo (ENGINEERING Environment, 2026)

Hyperspectral response and quantitative monitoring of soil organic carbon on the Loess Plateau - Sha Yang; Zhigang Wang; Chenzhi Zheng; Yuchao Yang; Jiancheng Zhang; Xingxing Qiao; William Rickard; Yu Zhao; Meichen Feng; Longmei Gao; Wude Yang; Chao Wang (Computers and Electronics in Agriculture, 2026)

Exopolysaccharides from Lactiplantibacillus plantarum Y12 enhance adhesion to HT-29 cells and gastrointestinal survival, and act synergistically with Y12 to alleviate DSS-induced colitis in mice by modulating the gut microbiota and repairing the intestinal barrier - Xiaochen Shi; Tianhao Zhang; Xueqi Lu; Meichen Sui; Zhiyan Wen; Yanfeng Tuo; Guangqing Mu; Yinglong Song (Food Bioscience, 2026)

Machine learning with augmented data for predicting bentonite swelling pressure - Wenyan Shi; Feng Zhang; Changdong Li; Qingbing Liu; Long Xu; Zhangrong Liu; Hangjing Zhou; Meichen Liu; Yuxian Jiang (Bulletin of Engineering Geology and the Environment, 2026)

A GDD-constrained allometric framework for UAV-based estimation of winter wheat aboveground biomass - Xinglong Duan; Bokun Hao; Zhigang Wang; Yidan Ding; Yufei Wang; Qianyu Wang; Zhenwei Yang; Chenbo Yang; Yu Zhao; Chao Wang; Lujie Xiao; Meijun Zhang; et al. (Computers and Electronics in Agriculture, 2026)

Rapid fractionation of moso bamboo using ternary deep eutectic solvent for integrated enzymatic hydrolysis and in situ treatment liquid gelation - Jiaying Li; Chengcheng Yuan; Meichen Zhang; Yingchao Wang; Feng Xu; Fengshan Zhang; Zongwei Guo; Hao Ma; Xingxiang Ji (Chemical Engineering Journal, 2026)

Spatiotemporal heterogeneity of carbon balance effects in China's population-shrinking cities amid urban transition - Jianwen Zhang; Meichen Fu; Yanqing Liang; Chaoran Zhao; Sijia Li; Feng Tang (Applied Geography, 2026)

Decoupling of arbuscular mycorrhizal fungi and soil organic carbon under nitrogen addition in terrestrial ecosystems: a meta-analysis - Andi Li; Jing Chen; Senhao Wang; Guangcan Yu; Meichen Xu; Anchi Wu; Jinhua Mao; Wei Zhang; Zhanfeng Liu; Juxiu Liu; Jiangming Mo; Mianhai Zheng (Frontiers of Earth Science, 2026)

Regulating mineral ions to enhance uranium phytoremediation by Macleaya cordata under synergistic effects of oxalic acid and Fusarium sp. A-2 - Meichen Li; Huang Yu; Tao Lang; Qinwen Deng; Weichao Zhao; Hui Zhang; Yuan Xue; Yongdong Wang; Dexin Ding; Nan Hu (Journal of Environmental Radioactivity, 2026)

Integrating leaf-scaled spectra and machine learning for rapid estimation of photosynthetic phenotypes across soybean genotypes - Chao Wang; Xiaobin Yan; Yan Bai; Jiaxue Zhang; Xinhui Guo; Xiaomei Zhang; Meichen Feng; William Rickard; Yu Zhao; Fangzhou Li; Chenbo Yang; Xiaokai Chen; et al. (Computers and Electronics in Agriculture, 2025)

The combination of ground hyperspectral and satellite multispectral with LSO-RF algorithm for enhanced inversion accuracy of heavy metal content in soil in coal mining areas - Meichen Liu; Meng Luo; Jing Gao; Shengwei Zhang; Yongting Han (Minerals Engineering, 2025)

Human activities challenge carbon storage in the Yangtze River Delta, China - Meichen Jiang; Xin Wang; Pengcheng Liu; Nana Zhang (Journal of Environmental Management, 2025)

Small lakes, big improvements: a multi-decadal assessment of policy and climate impacts on chlorophyll-a in China - Sijia Li; Hong Yang; Ge Liu; Dehua Mao; Zongming Wang; Haiqing Liao; Lele Zhang; Haoyun Zhou; Meichen Ji; Kaishan Song (Science Bulletin, 2025)

Monitoring the growth status of winter wheat by using the machine learning algorithm and the fusion of spectral and texture features derived from the UAV remote sensing - YiMing Su; XiaoBin Yan; Hao Li; ZiHao Liang; ShuangMei Zhao; Ping Chen; Zhen Zhang; XingXing Qiao; Yu Zhao; MeiChen Feng; Fahad Shafiq; XiaoYan Song; et al. (Computers and Electronics in Agriculture, 2025)

Under the combined application of selenium and sulfur, sulfur does not interfere with selenite uptake in Tartary buckwheat - Shangqun Ji; Panfeng Liu; Shuangmei Zhao; Minghui Dai; Wenbo Han; Zhen Zhang; Chao Wang; Fahad Shafiq; Xingxing Qiao; Lujie Xiao; Meichen Feng; Meijun Zhang; et al. (Food Chemistry, 2025)

Two-dimensional surface induced strategy enabling high-quality halide perovskite thin film growth via vapor-solid reactions - Meichen Liu; Shenghan Hu; Changyu Duan; Xinyu Deng; Yichen Dou; Mengjun Liu; Yuanbo Song; Tiancan Zhang; Guijie Liang; Zhiliang Ku (Chemical Engineering Journal, 2025)

A galacturonan from sea buckthorn (Hippophae rhamnoides L.) berry modulates dyslipidemia by promoting hepatic lipolysis and mitochondrial oxidation - Yunpeng Sun; Weifeng Ni; Dongyi Wang; Jixiang Ren; Daqing Zhao; Shiting Yu; Shichao Liu; Shaojie Zhang; Siming Wang; Weinan Wang; Meichen Liu (Carbohydrate Polymers, 2025)

Hydrochar relieved long chain fatty acids (LCFA) inhibition in continuous anaerobic reactor treating food waste - Meichen Sun; Yafei Cheng; Taoyang Jiang; Yalei Zhang; Shicheng Zhang; Gang Luo (Bioresource Technology, 2025)

An integrated CFD and CNN-GRU approach for accurate prediction of PM2.5 in greenhouse environments of Northeast China - Shuo Zhang; Li Guo; Haiye Yu; Bo Zhang; Meichen Chen; Lei Zhang; Dawei Li; Yuanyuan Sui (Building and Environment, 2025)

Plant morphological and physiological traits are stable in a nitrogen-saturated tropical forest after 18-year nitrogen additions - Guangcan Yu; Jing Chen; Andi Li; Senhao Wang; Liang Song; Xianmeng Shi; Junhua Yan; Meichen Xu; Yuewei Xue; Xiankai Lu; Wei Zhang; Juan Huang; et al. (Plant and Soil, 2025)

Hyperspectral assessment of bacterial blight disease in red kidney beans by feature selection and machine learning algorithms - Xingxing Qiao; Jiachen Wang; Binghan Jing; Xin Zhang; Yaoxuan Jia; Kunming Huang; Wude Yang; Meichen Feng; Zhen Zhang; Yu Zhao; Fahad Shafiq; Lujie Xiao; et al. (Precision Agriculture, 2025)

Comparative analysis of the effects of different dimensionality reduction algorithms on hyperspectral estimation of total nitrogen content in wheat soils - Juan Bai; Shiyou Zhu; Yingchao Hao; Xinzhe Li; Chenbo Yang; Chao Wang; Xingxing Qiao; Meichen Feng; Lujie Xiao; Xiaoyan Song; Meijun Zhang; Sha Yang; et al. (European Journal of Agronomy, 2025)

Pyrochar relieved the negative effects of hydrothermal pretreatment of sludge on vivianite production in anaerobic digestion - Yafei Cheng; Xiaofeng Xu; Yan Shi; Meichen Sun; Chao Zhang; Zhijian Shi; Yalei Zhang; Shicheng Zhang; Gang Luo (Chemical Engineering Journal, 2025)

Quercetin attenuates DEHP-induced pyroptosis and programmed necrosis in chicken duodenum through regulation of the TLR4/MyD88/NF-κB pathway - Ruirui Xie; Tong Xu; Yilin Yin; Meichen Liu; Chenxi Huang; Wenwen Zhang; Shu Li (Environmental Pollution, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

Mechanism of decolorization and degradation of direct brown D3G by a halo-thermophilic consortium - Wenying Wang; Zuotao Zhang; Meichen Sun; Chenlai Li; Mengdi Yan; Chongyang Wang (Extremophiles, 2025)

A new feature selection algorithm combining genetic algorithm, exponential decay function, and machine learning to realize hyperspectral estimation of winter wheat leaf area index - Chenbo Yang; Juan Bai; Hui Sun; Rutian Bi; Lifang Song; Amjad Muhammad; Chao Wang; Yu Zhao; Wude Yang; Lujie Xiao; Meijun Zhang; Xiaoyan Song; et al. (Computers and Electronics in Agriculture, 2025)

Evaluating the potential of airborne hyperspectral imagery in monitoring common beans with common bacterial blight at different infection stages - Binghan Jing; Jiachen Wang; Xin Zhang; Xiaoxiang Hou; Kunming Huang; Qianyu Wang; Yiwei Wang; Yaoxuan Jia; Meichen Feng; Wude Yang; Chao Wang (Biosystems Engineering, 2025)

Molecular disruptions in microalgae caused by Acidithiobacillus ferrooxidans: Photosynthesis, oxidative stress, and energy metabolism in acid mine drainage - Meichen Wang; Zhengbo Yue; Rui Deng; Zhixiang She; Lu Zhang; Fan Yang; Jin Wang (Water Research, 2025)

Serum arsenic augments gallstone risk in Henan rural cohort with multiple metal exposure - Qian Zhang; Yating Li; Han Hu; Meichen Tian; Tingting Cao; Hui Wu; Weidong Wu; Guofu Zhang (Science of The Total Environment, 2024)

Quercetin attenuates SiO2-induced ZBP-1-mediated PANoptosis in mouse neuronal cells via the ROS/TLR4/NF-κb pathway - Meichen Liu; Meichen Gao; Xu Shi; Yilin Yin; Huanyi Liu; Ruirui Xie; Chenxi Huang; Wenwen Zhang; Shiwen Xu (Journal of Environmental Management, 2024)

Syntrophic propionate degradation in anaerobic digestion facilitated by hydrochar: Microbial insights as revealed by genome-centric metatranscriptomics - Zhijian Shi; Chao Zhang; Meichen Sun; Muhammad Usman; Yong Cui; Shicheng Zhang; Bingjie Ni; Gang Luo (Environmental Research, 2024)

Metagenomic insights into the enhanced methane production by hydrochar at varied propionate concentrations - Taoyang Jiang; Huu Hao Ngo; Meichen Sun; Chao Zhang; Shicheng Zhang; Zhijian Shi; Gang Luo (Chemical Engineering Journal, 2024)

Changes in the magnetic properties of a tropical red soil following the conversion of forest into agricultural land - Meichen Wang; Fengrui Li; Haixia Li; Xiaoling Zhang; Shiyu Li; Gangqiang Li; Yudong Chen; Yang Wang; Jingyuan Hu; Junmin Ye (Journal of Applied Geophysics, 2024)

Evolutionary causes of global patterns of species richness in regional fern floras across the world - Hong Qian; Michael Kessler; Jian Zhang; Yi Jin; Meichen Jiang (Journal of Biogeography, 2024)
Aim Globally, biodiversity is unevenly distributed, as a result of varying environmental conditions and regionally different historical processes. The influence of the latter on current diversity patterns is poorly understood. We explore geographic patterns of matches and mismatches between phylogenetic relatedness metrics measuring different depths of evolutionary history and investigate the effects of evolutionary legacy at different evolutionary depths on species density of ferns. Methods We divided the globe into 392 geographic regions on land, and collated species lists of ferns for each geographic region. We related species richness to phylogenetic metrics reflecting different depths of evolutionary history (standardized effect sizes of mean nearest taxon distance and mean pairwise distance, MNTD ses and MPD ses , respectively) for ferns in regional floras across the world. Location Global. Time Period Current. Taxon Ferns. Results We show that different centers of fern diversity have strikingly different phylogenetic composition. We find that overall fern species diversity is negatively correlated with both MNTD ses and MPD ses , so that regions with high species diversity tend to have clustered species assemblages, whereas species‐poor regions tend to have overdispersed species assemblages. At the global extent, MNTD ses and MPD ses together explained 62.2%, 19.3%, and 65.7% of the variation in species diversity for all ferns as a whole, non‐polypod ferns, and polypods, respectively. Main Conclusions Our study suggests that current geographic patterns of fern species richness are driven, at least in part, by evolutionary history of ferns, which varies among biogeographic regions.

Green pretreatment of lignocellulosic biomasses via deep eutectic solvents - Yingxia Guo; Jiaxin Zhang; Chuya Wang; Meichen Liu; Jiansong You; Lei Yin; Meiyun Shi (Sustainable Chemistry and Pharmacy, 2024)

Characteristics of the presence and migration patterns of DOM between ice and water in the cold and arid Daihai Lake - Ting Pan; Yimeng Zhang; Fang Yang; Haiqing Liao; Weiying Feng; Fuhong Sun; Weilong Jiang; Qianqian Wang; Meichen Ji; Chenglei Yang; Matti Leppäranta (Science of The Total Environment, 2024)

Combined use of spectral resampling and machine learning algorithms to estimate soybean leaf chlorophyll - Chunrui Gao; Hao Li; Jiachen Wang; Xin Zhang; Kunming Huang; Xiaoyan Song; Wude Yang; Meichen Feng; Lujie Xiao; Yu Zhao; Fahad Shafiq; Chao Wang; et al. (Computers and Electronics in Agriculture, 2024)

Excellent solar-driven interface evaporation by an oil repellence Janus photothermal membrane for oily wastewater treatment - Wenwen Luo; Jia Zhang; Meichen Liu; Anli Yi; Rui Jiao; Zhaoqi Zhu; Jiyan Li; Hanxue Sun; An Li (Chemical Engineering Journal, 2024)

Metagenomic analysis towards understanding the effects of ammonia on chain elongation process for medium chain fatty acids production - Zheng Chen; Zhijian Shi; Yalei Zhang; Yan Shi; Meichen Sun; Yong Cui; Shicheng Zhang; Gang Luo (Bioresource Technology, 2024)

Zinc Inhibits Lead-Induced Oxidative Stress and Apoptosis of ST Cells Through ROS/PTEN/PI3K/AKT Axis - Haoyu Zhang; Kexin Sun; Meichen Gao; Shiwen Xu (Biological Trace Element Research, 2024)

Efficient prediction of SOC and aggregate OC components by continuous wavelet transform spectra under different feature selection methods - Sha Yang; Zhigang Wang; Caiyu Ji; Yingchao Hao; Zihao Liang; Xiaobin Yan; Xingxing Qiao; Meichen Feng; Lujie Xiao; Xiaoyan Song; Meijun Zhang; Guangxin Li; et al. (Computers and Electronics in Agriculture, 2024)

ERK/PKM2 Is Mediated in the Warburg Effect and Cell Proliferation in Arsenic-Induced Human L-02 Hepatocytes - Fanshuo Yin; Xin Zhang; Zaihong Zhang; Meichen Zhang; Yunyi Yin; Yanmei Yang; Yanhui Gao (Biological Trace Element Research, 2024)

Long‐term nitrogen and phosphorus addition have stronger negative effects on microbial residual carbon in subsoils than topsoils in subtropical forests - Linjie Fan; Yuewei Xue; Donghai Wu; Meichen Xu; Andi Li; Baixin Zhang; Jiangming Mo; Mianhai Zheng (Global Change Biology, 2024)
Highly weathered lowland (sub)tropical forests are widely recognized as nitrogen (N)‐rich and phosphorus (P)‐poor, and the input of N and P affects soil carbon (C) cycling and storage in these ecosystems. Microbial residual C (MRC) plays a crucial role in regulating soil organic C (SOC) stability in forest soils. However, the effects of long‐term N and P addition on soil MRC across different soil layers remain unclear. This study conducted a 12‐year N and P addition experiment in two typical subtropical plantation forests dominated by Acacia auriculiformis and Eucalyptus urophylla trees, respectively. We measured plant C input (fine root biomass, fine root C, and litter C), microbial community structure, enzyme activity (C/N/P‐cycling enzymes), mineral properties, and MRC. Our results showed that continuous P addition reduced MRC in the subsoil (20–40 cm) of both plantations ( A. auriculiformis : 28.44% and E. urophylla : 28.29%), whereas no significant changes occurred in the topsoil (0–20 cm). N addition decreased MRC in the subsoil of E. urophylla (25.44%), but had no significant effects on A. auriculiformis . Combined N and P addition reduced MRC (34.63%) in the subsoil of A. auriculiformis but not in that of E. urophylla . The factors regulating MRC varied across soil layers. In the topsoil (0–10 cm), plant C input (the relative contributions to the total variance was 20%, hereafter) and mineral protection (47.2%) were dominant factors. In the soil layer of 10–20 cm, both microbial characteristics (41.3%) and mineral protection (32.3%) had substantial effects, whereas the deeper layer (20–40 cm) was predominantly regulated by microbial characteristics (37.9%) and mineral protection (18.8%). Understanding differential drivers of MRC across soil depth, particularly in deeper soil layers, is crucial for accurately predicting the stability and storage of SOC and its responses to chronic N enrichment and/or increased P limitation in (sub)tropical forests.

Structural and mineralogical variation upon reoxidation of reduced Fe-bearing clay minerals during thermal activation - Wenwen Zhang; Xiaodong Li; Yao Zhao; Zongquan Sun; Meichen Yao; Xuefei Zhou; Fasheng Li; Fujun Ma; Qingbao Gu (Science of The Total Environment, 2023)

The disruption of blood-brain barrier induced by long-term arsenic exposure is associated with the increase of MMP-9 and MMP-2: The characteristics are similar to those caused by senescence - Man Lv; Xinbo Ma; Kunyu Zhang; Meichen Zhang; Yi Ji; Lin Cheng; Xinhua Shao; Ziqiao Guan; Jia Cui; Yanhui Gao; Yang Liu; Yanmei Yang; et al. (Chemico-Biological Interactions, 2023)

Association between arsenic (+3 oxidation state) methyltransferase gene polymorphisms and arsenic methylation capacity in rural residents of northern China: a cross-sectional study - Meichen Zhang; Haili Xu; Qun Lou; Zaihong Zhang; Xin Zhang; Fanshuo Yin; Man Lv; Ying Zhang; Yunyi Yin; Yanhui Gao; Xiaona Liu; Yanmei Yang (Archives of Toxicology, 2023)

Association between ADAMTS14_rs4747096 gene polymorphism and bone mineral density of Chinese Han population residing in fluorine exposed areas in ShanXi Province, China - Ming Qin; Yue Gao; Meichen Zhang; Junhua Wu; Yang Liu; Yuting Jiang; Xiaodi Zhang; Xin Wang; Yanmei Yang; Yanhui Gao (Environmental Science and Pollution Research, 2023)

Multivariate prediction of soil aggregate-associated organic carbon by simulating satellite sensor bands - ChunRui Gao; XiaoBin Yan; XingXing Qiao; KunXi Wei; XiaoMei Zhang; Sha Yang; Chao Wang; WuDe Yang; MeiChen Feng; LuJie Xiao; MeiJun Zhang; Zhou Zhang; et al. (Computers and Electronics in Agriculture, 2023)

Genome-centric metagenomic analysis revealed the microbial shifts in response to long-chain fatty acids (LCFA) in anaerobic digestion with hydrochar - Meichen Sun; Chao Zhang; Zhijian Shi; Chen Zhang; Shicheng Zhang; Gang Luo (Chemical Engineering Journal, 2023)

Enhanced adsorption and co-adsorption of heavy metals using highly hydrophilicity amine-functionalized magnetic hydrochar supported MIL-53(Fe)-NH2: performance, kinetics, and mechanism studies - Xin Luo; Haiying Du; Xiaochao Zhang; Bo Tang; Meichen Zhang; Heng Kang; Yanqi Ma (Environmental Science and Pollution Research, 2023)

SIRT1/P53 pathway is involved in the Arsenic induced aerobic glycolysis in hepatocytes L-02 cells - Meichen Zhang; Zaihong Zhang; Qun Lou; Xin Zhang; Fanshuo Yin; Yunyi Yin; Haili Xu; Ying Zhang; Chenlu Fan; Yanhui Gao; Yanmei Yang (Environmental Science and Pollution Research, 2023)

Evaluation of data pre-processing and regression models for precise estimation of soil organic carbon using Vis–NIR spectroscopy - Yaxin Wang; Sha Yang; Xiaobin Yan; Chenbo Yang; Meichen Feng; Lujie Xiao; Xiaoyan Song; Meijun Zhang; Fahad Shafiq; Hui Sun; Guangxin Li; Wude Yang; et al. (Journal of Soils and Sediments, 2023)

Verniciflavanol A, a profisetinidin-type-4-arylflavan-3-ol from toxicodendron vernicifluum protects SH-SY5Y cells against H2O2-Induced oxidative stress - Meichen Li; Yunqiang Zhang; Tingting Han; Lu Guan; Dongxue Fan; Qinke Wu; Jianyu Liu; Yongnan Xu; Yanhua Fan (Phytochemistry, 2023)

Spillover-feedback effects of employment, energy, economy and environment (4E) between domestic-owned and foreign-invested enterprises: Taking China as an example - Junjun Hou; Youfu Yue; Qian Wang; Jiabai Ye; Meichen Zhang (Journal of Cleaner Production, 2023)

Mice kidney biometabolic process analysis after cantharidin exposure using widely-targeted metabolomics combined with network pharmacology - Tianmu He; Lijuan Xiong; Yixin Zhang; Rong Yan; Ming Yu; Meichen Liu; Liu Liu; Cancan Duan; Xiaofei Li; Jianyong Zhang (Food and Chemical Toxicology, 2023)

Mechanism of evodiamine blocking Nrf2/MAPK pathway to inhibit apoptosis of grass carp hepatocytes induced by DEHP - Yutian Lei; Wenyue Zhang; Meichen Gao; Hongjin Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Hyperspectral monitoring of soil urease activity under different water regulation - Chenbo Yang; Meichen Feng; Lifang Song; Binghan Jing; Yongkai Xie; Chao Wang; Mingxing Qin; Wude Yang; Lujie Xiao; Jingjing Sun; Meijun Zhang; Xiaoyan Song; et al. (Plant and Soil, 2022)

Research for type 2 diabetes mellitus in endemic arsenism areas in central China: role of low level of arsenic exposure and KEAP1 rs11545829 polymorphism - Chenlu Fan; Zaihong Zhan; Xin Zhang; Qun Lou; Ning Guo; Mengyao Su; Yue Gao; Ming Qin; Liaowei Wu; Wei Huang; Meichen Zhang; Fanshuo Yin; et al. (Archives of Toxicology, 2022)

Isolation of a new monoterpenoid glycoside from Anhua dark tea based on an NMR-guided method and its cytotoxic activity against MDA-MB-231 and SH-SY5Y cell lines - Yunqiang Zhang; Jianyu Liu; Miao Chen; Yanhua Fan; Meichen Li; Andong Wang; Gaigai Liu; Yongnan Xu; Xuhong Ren; Yan Xiao (Natural Product Research, 2022)

AoATG5 plays pleiotropic roles in vegetative growth, cell nucleus development, conidiation, and virulence in the nematode-trapping fungus Arthrobotrys oligospora - Duanxu Zhou; Yingmei Zhu; Na Bai; Le Yang; Meihua Xie; Jiangliu Yang; Meichen Zhu; Ke-Qin Zhang; Jinkui Yang (Science China Life Sciences, 2022)

Risks Assessment Associated with Different Sources of Metals in Abandoned Soil of Zhuxianzhuang Coal Mine, Huaibei Coalfield (Anhui, China) - Hongxia Fang; Herong Gui; Jun Li; Hao Yu; Meichen Wang; Yaqi Jiang; Chunlei Wang; Chen Chen; Yaru Zhang; Yiheng Huang (Bulletin of Environmental Contamination and Toxicology, 2021)

Comparative transcriptomic and metabolomic analyses of carotenoid biosynthesis reveal the basis of white petal color in Brassica napus - Ledong Jia; Junsheng Wang; Rui Wang; Mouzheng Duan; Cailin Qiao; Xue Chen; Guoqiang Ma; Xintong Zhou; Meichen Zhu; Fuyu Jing; Shengsen Zhang; Cunmin Qu; et al. (Planta, 2021)
Main conclusion The molecular mechanism underlying white petal color in Brassica napus was revealed by transcriptomic and metabolomic analyses. Abstract Rapeseed ( Brassica napus L.) is one of the most important oilseed crops worldwide, but the mechanisms underlying flower color in this crop are known less. Here, we performed metabolomic and transcriptomic analyses of the yellow-flowered rapeseed cultivar ‘Zhongshuang 11’ (ZS11) and the white-flowered inbred line ‘White Petal’ (WP). The total carotenoid contents were 1.778-fold and 1.969-fold higher in ZS11 vs. WP petals at stages S2 and S4, respectively. Our findings suggest that white petal color in WP flowers is primarily due to decreased lutein and zeaxanthin contents. Transcriptome analysis revealed 10,116 differentially expressed genes with a fourfold or greater change in expression ( P -value less than 0.001) in WP vs. ZS11 petals, including 1,209 genes that were differentially expressed at four different stages and 20 genes in the carotenoid metabolism pathway. BnNCED4b , encoding a protein involved in carotenoid degradation, was expressed at abnormally high levels in WP petals, suggesting it might play a key role in white petal formation. The results of qRT-PCR were consistent with the transcriptome data. The results of this study provide important insights into the molecular mechanisms of the carotenoid metabolic pathway in rapeseed petals, and the candidate genes identified in this study provide a resource for the creation of new B. napus germplasms with different petal colors.

Spatiotemporal variation and influencing factors of vegetation cover in the ecologically fragile areas of China from 2000 to 2015: a case study in Shaanxi Province - Dingrao Feng; Jinman Wang; Meichen Fu; Guangchao Liu; Min Zhang; Rongbin Tang (Environmental Science and Pollution Research, 2019)

Occurrence and distribution of selected antibiotics in the surface waters and ecological risk assessment based on the theory of natural disaster - Sijia Li; Hanyu Ju; Jiquan Zhang; Peng Chen; Meichen Ji; Jianhua Ren; Shuyun Zhao (Environmental Science and Pollution Research, 2019)

The relationship of chromophoric dissolved organic matter parallel factor analysis fluorescence and polycyclic aromatic hydrocarbons in natural surface waters - Sijia Li; Ya’nan Chen; Jiquan Zhang; Kaishan Song; Guangyi Mu; Caiyun Sun; Hanyu Ju; Meichen Ji (Environmental Science and Pollution Research, 2018)

Identification of novel reference genes using sika deer antler transcriptome expression data and their validation for quantitative gene expression analysis - Meichen Liu; Baojin Yao; Hui Zhang; Huanyu Guo; Dongyang Hu; Qun Wang; Yu Zhao (Genes & Genomics, 2014)

Pattern dynamics of thermal-environment effect during urbanization: A case study in Shenzhen City, China - Miaomiao Xie; Yanglin Wang; Meichen Fu; Dingxuan Zhang (Chinese Geographical Science, 2013)

De novo characterization of the antler tip of Chinese Sika deer transcriptome and analysis of gene expression related to rapid growth - Baojin Yao; Yu Zhao; Qun Wang; Mei Zhang; Meichen Liu; Hailong Liu; Juan Li (Molecular and Cellular Biochemistry, 2012)

Sequencing and de novo analysis of the Chinese Sika deer antler-tip transcriptome during the ossification stage using Illumina RNA-Seq technology - Baojin Yao; Yu Zhao; Haishan Zhang; Mei Zhang; Meichen Liu; Hailong Liu; Juan Li (Biotechnology Letters, 2012)

Land Use-Based Landscape Planning and Restoration in Mine Closure Areas - Jianjun Zhang; Meichen Fu; Ferri P. Hassani; Hui Zeng; Yuhuan Geng; Zhongke Bai (Environmental Management, 2011)